PENERAPAN BIRTH BALL DENGAN TEKNIK PELVIC ROCKING TERHADAP LAMA PERSALINAN PADA KALA I FASE AKTIF - Diah Evawanna Anuhgera; Nikmah Jalilah Ritonga; Riris Sitorus; Juni Mariati Simarmata (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
A comfortable childbirth is the dream of mothers. Faster delivery progress can lead to quality midwifery care. Birth ball is a tool that can be used by mothers to position the pelvis properly, especially applied the pelvic rocking technique. This review study aimed to evaluate the evidence regarding the effect of using birth ball with pelvic rocking in duration of labor in kala I active phase. This study followed a quasi experimental research design with posttest control group design.The sample consisted of 12 treatment people dan 12 controls with the purposive sampling.Partograph was measured duration of labor in kala I active phase. The difference in duration of labor for the treatment and control group were tested with Mann Whitney. There was a difference in the effect of using a birth ball with pelvic rocking technique in length of labor in kala I active phase in the treatment and control groups with p-value 0.001. The use of birth ball with pelvic rocking technique is evidence to speed the duration of labor in kala I active phase. Birth ball with pelvic rocking are recommended to be use an alternative to speed the duration of labor in kala I active phase in midwifery services